Alternativas de integración para la Argentina: Un análisis de equilibrio general - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2002)
– Argentina has an ambitious trade negotiations agenda for the coming years, both at the multilateral level (WTO) and the regional level (FTAA, MERCOSUR-EU, etc.). In this paper an initial assessment is made of the economic impact of the concessions (on the part of Argentina and of the future partners) involved in such agreements. For this purpose, a Computable General Equilibrium (CGE) model is used, which reflects the interrelations between all economic sectors and identifies the winners and losers after trade liberalization. The model used was developed at the Foreign Ministry's International Economy Centre (CEI), based on the Global Trade Analysis Project (GTAP) model. In the CEI version, the model adds nonstandard features, such as growing returns to scale in the manufacturing sectors, capital accumulation in the medium term and a positive relationship between trade openness and the productivity of the factors involved. In order to make the model operational (calibration), the latest GTAP database version is used. With a deliberate focus on the negotiations agenda of Argentina, five trade integration scenarios were simulated: (i) Free Trade Area of the Americas (FTAA), (ii) A free trade agreement between the countries of MERCOSUR and the European Union, iii) A combination of (i) and (ii) above, (iv) A free trade agreement between the countries of MERCOSUR and the United States (4 + 1) and v) Free world trade. In general terms, these agreements are simulated by setting bilateral tariff rates at zero. Accordingly, the simulated scenarios are the upper limit of the results that could be obtained from the simulated trade liberalization agreements. The simulations use a GTAP data base aggregation of sixteen sectors and ten regions. This enables the detection of the main aggregate, sectorial effects and the trade patterns of the trade integration scenarios.
Keywords: 330; Handelsabkommen; Argentinien; Makroökonomischer Einfluss